INSTITUTIONAL ASPECTS OF EUROPEAN ECONOMIC POLICY COORDINATION MECHANISMS: THE IMPLICATION FOR SERBIA (EU and comparative law issues and challenges series (ECLIC), 2020)
The subject of analysis in this paper is to review the institutional aspects of coordination mechanisms for economic policy in the European Union. In this context, the first part of the article defines the concept of coordination, the benefits versus the competition, the goals and the principles on which mechanisms are placed. In the second part of paper points to the impact of the mechanism for coordination of economic policy in Serbia, costs and benefits of the coordination process, i.e. primarily in the light of the new wave of coordination which started with the new model of economic governance during the global crisis embodied in the provisions of the European semester, the European Stabilisation Mechanism and the Treaty on Stability, Coordination and Governance in the Economic and Monetary Union. The central hypothesis is based on the fact that Serbia its economic policy must shape according to European coordination mechanisms in the broadest sense, and not only in the field of monetary and fiscal policy, but also other segments of structural macroeconomic policies (labour market, as well as in the new areas such as environmental policy and cohesion policy) to achieve sustainable economic development. Although the domestic economic policymakers have done a lot on that plan, there is still a practical and logical need for the harmonisation of specific segments of economic policy and reducing the time lag in the implementation of the actions of economic policy.